HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI SDN PURWASEDAR - Azahra Fajarianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the relationship between learning motivation and students’ learning outcomes in the Natural and Social Sciences (IPAS) subject at SDN Purwasedar. Learning motivation is an important internal factor that influences students’ ability to achieve optimal learning outcomes. This research employed a quantitative approach using a correlational method. The subjects of this study were students of SDN Purwasedar selected through a specific sampling technique. Data on learning motivation were collected using a questionnaire, while learning outcomes data were obtained from students’ IPAS scores. The data were analyzed using correlation analysis to identify the relationship between the two variables. The results of the study indicate that there is a significant relationship between learning motivation and students’ learning outcomes in the IPAS subject. Higher learning motivation is associated with better learning outcomes. Therefore, it can be concluded that learning motivation plays an important role in improving students’ learning outcomes. This study is expected to provide useful information for teachers and schools in developing strategies to enhance students’ learning motivation in order to achieve better academic results.